Do digital influencers successfully contribute to reducing the gap between customers and companies? - Isaac Moreira; Paulo Stenzel; João M. Lopes; José Oliveira (BBR: Brazilian Business Review)
The purpose of this research is to analyze the role of digital influencers in the construction of relationships between companies and consumers. A qualitative methodology was used, whereby seven Portuguese service providers were interviewed. The results obtained demonstrate that companies’ hire digital influencers to publicize their products, create notoriety, build a trustworthy image, and increase sales. It was also found that the most used platform for digital strategies is Instagram, due to its ease of communication and number of active users. Furthermore, it is important to emphasize that the traceability of sales related to digital influencers is quantifiable through tools such as Google Analytics, discount coupons, number of site visits generated, and also the increment of followers on digital promotions days. This research contributes to scientific knowledge as it validates the theoretical constructs developed on the role of digital influencers in the establishment of relationships between brands and consumers and confronts them with the business reality. Finally, some suggestions for future line of investigation are presented.